1986
DOI: 10.1126/science.3787252
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T Cell Receptor Gamma Chain Expression in a Subset of Murine Thymocytes

Abstract: While much information exists about the structure and function of the clonally distributed T cell receptor (TCR) alpha beta heterodimer, little is known about the gamma protein, the product of a third rearranging TCR gene. An antiserum to a carboxyl-terminal peptide common to several of the murine gamma chain constant regions and a monoclonal antibody to the murine T3 complex were used to identify products of this TCR gene family in a subpopulation of Lyt2-, L3T4- thymocytes. This subpopulation does not expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
103
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 194 publications
(109 citation statements)
references
References 33 publications
5
103
1
Order By: Relevance
“…To determine the approximate frequency of 8 rearrangements in thymic y/8 cells, we analyzed the rearrangements present in DNA from an enriched population of such cells (50-80% y/8 cells) isolated by short-term (3 d) culture in a lymphokine cocktail (4) . Because most of these cells express a y/8 receptor, quantitation of various 8 rearrangements represents an approach to determining the usage and diversity of V8 genes in the population .…”
Section: Resultsmentioning
confidence: 99%
“…To determine the approximate frequency of 8 rearrangements in thymic y/8 cells, we analyzed the rearrangements present in DNA from an enriched population of such cells (50-80% y/8 cells) isolated by short-term (3 d) culture in a lymphokine cocktail (4) . Because most of these cells express a y/8 receptor, quantitation of various 8 rearrangements represents an approach to determining the usage and diversity of V8 genes in the population .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, TCRa/Q expression increases throughout T cell ontogeny concomitantly with the acquisition of CD4 and/or CD8 molecules by mature T cells, expression of TCRy/S being restricted to a small population of CD4" CD8 -adult thymocytes and peripheral T cells (3,4) . These findings suggest that y/8-bearing CD4 -CD8 -cells may define a separate T cell lineage whose intrathymic development precedes that of classical a/a mature T cells (21,22) . Nonetheless, the presence of y gene rearrangements in mature a/0-bearing T cells (23), as well as the finding of partial a gene rearrangements in TCRy/S+ cells processes remain poorly understood, and precursor-product relationships involving the various intrathymic subpopulations continue to be disputed, making it difficult to establish direct correlations between the described patterns of TCR gene expression and a functional pathway of T cell development.…”
mentioning
confidence: 87%
“…Results and Discussion Six TCR-7/6-expressing hybridomas (1C6.F11 and 1H11 .B9 of C3H/HeN origin and DN12 .1, DN7.1, DN7 .3, and DN2 .3 of C57BL/6 origin) were used in this study. Earlier studies (2,6,12,13) have indicated that all these hybridomas express glycosylated y chains that are not derived from Vy-Cy4 transcripts since the antiserum used to detect these y chains does not react with Cy4 chains (nomenclature according to Garman et al, [10]). Furthermore, since the Cy3 locus is a pseudogene (8) and, at least for the C57BL/6 mice, V71 .2-C"y2 transcripts would result in nonglycosylated y chains (19), these hybridomas most likely express y chains derived from Vy-CyI transcripts.…”
Section: Methodsmentioning
confidence: 99%